Acoustic Nanomotors for Detection of Human Papillomavirus–Associated Head and Neck Cancer. (24th September 2019) - Qualliotine, Jesse R.; Bolat, Gulcin; Beltrán‐Gastélum, Mara; de Ávila, Berta Esteban‐Fernández; Wang, Joseph; Califano, Joseph A.
Abstract : Objective: Human papillomavirus (HPV)–associated oropharyngeal cancer (OPC) is a lethal disease with increasing incidence; however, technologies for early detection are limited. Nanomotors are synthetic nanostructures that can be powered by different mechanisms and functionalized for specific applications, such as biosensing. The objective of this investigation was to demonstrate an in vitro proof of concept for a novel nanomotor‐based cancer detection approach toward in vivo detection of HPV‐OPC. Study Design: In vitro cell line incubated with ultrasound‐propelled nanomotors. Setting: Basic science and engineering laboratories. Subjects and Methods: Ultrasound‐powered gold nanowire nanomotors were functionalized with graphene oxide and dye‐labeled single‐stranded DNA for the specific intracellular detection of HPV16 E6 mRNA transcripts. Nanomotors were incubated with HPV‐positive or HPV‐negative human OPC cells under static conditions or with an applied ultrasound field for 15 minutes. The resulting intracellular fluorescence was assessed with fluorescence microscopy and analysis software. Results: Nanomotors incubated with RNA extracted from HPV‐positive OPC cells resulted in 60.7% of maximal fluorescence recovery, while incubation with RNA extracted from HPV‐negative cells produced negligible fluorescence. Nanomotor incubation with intact HPV‐negative cells produced minimal fluorescence (0.01 au), while incubation with HPV‐positive cells produced a detectable signal (0.43 au) under static conditions and had 2.3‐times greater intensity when powered with ultrasound. Conclusion: Acoustically powered nanomotors can successfully identify HPV16 E6 mRNA transcripts extracellularly and within intact cells. This work represents the first step toward a novel, practical approach to address the challenge of visually detecting HPV‐OPC in real time.